Evolutionary Expression of HER2 Conferred by Chromosome Aneuploidy on Circulating Gastric Cancer Cells Contributes to Developing Targeted and Chemotherapeutic Resistance - Li, Yilin; Zhang, Xiaotian; Liu, Dan; Gong, Jifang; Wang, Daisy Dandan; Li, Shan; Peng, Zhi; Li, Yanyan; Wang, Xiaojuan; Lin, Peter Ping; Li, Min; Shen, Lin (Clinical cancer research, 2018)
Purpose: Previous human epidermal growth factor receptor-2 (HER2)-derived resistance studies were based on ex vivo models, which could not mirror evolutionary expression of HER2 during therapy. To investigate dynamic expression of HER2 and its contribution to developing therapeutic resistance conferred by chromosome aneuploidy, both the HER2 phenotype and chromosome 8 (Chr 8) aneuploidy on circulating tumor cells (CTC) were coexamined in advanced gastric cancer (AGC) patients. Experimental Design: A total of 115 AGC patients, including 56 of histopathologic HER2+ (hHER2+) subjects who received first-line HER2-targeted therapy plus chemotherapy, and 59 of hHER2− patients who received chemotherapy alone, were prospectively enrolled. Both HER2 phenotype and Chr8 aneuploidy of CTCs in patients were coexamined by HER2-iFISH during therapy. Results: A fluctuated positive HER2 phenotype on CTCs (cHER2+) was revealed, showing cHER2+ at different time intervals during treatment. Acquisition of the cHER2+ phenotype in 91.0% of hHER2+ and 76.2% hHER2− patients was demonstrated to correlate with development of resistance to trastuzumab-targeted therapy for hHER2+ patients and chemotherapy alone for hHER2− patients. Aneuploid Chr8 was demonstrated to participate in the acquisition of the cHER2+ phenotype, which provides a growth advantage to HER2+ CTCs against therapeutic pressure, leading to the development of therapeutic resistance. Conclusions: Compared with low positivity of conventional histopathologic hHER2 examination routinely performed once, significant higher positivity of cHER2+ on CTCs was observed. Continuously examining cHER2 shows unique advantages with respect to monitoring therapeutic resistance in real time in carcinoma patients. Moreover, contribution of chromosome aneuploidy to the phenotypic evolution of HER2 expression on CTCs may help elucidate underlying mechanisms of developing therapeutic resistance. Clin Cancer Res; 24(21); 5261–71. ©2018 AACR.